(untitled) (Journal of Engineering and Health Sciences, 2023)
Islamic University Institutions hostel maintenance management is essential to prolong the building life cycle and reduce the company loss. When University hostel is neglected, defects can occur which may result in extensive and unavoidable damage to the building fabric or structure. The objective of this study is to Islamic University Institutions hostel in Malaysia to find the maintenance problems used the snapshot model is to determine the major dominant fault, cause of fault, prevention and consequence analysis. The defect and the problem face will be collected and noted in a check list. This will be done by questionnaires and distributed to all service users in Islamic University Institutions hostel management student hostel. Hence, this paper is focusing on the Islamic University Institutions hostel management used snapshot model is to identify and determine the major dominant fault, cause of fault, prevention and consequence analysis which the aim is to reduce the downtime of plant items taking into account the possible impact of a failure in terms of cost. The analysis shows that the hostel building contributed to the most problematic area in Islamic University Institutions hostel based on snapshot model is a kind of hierarchical analysis where all possible failures are classified into different levels and conclude the major dominant fault, cause of fault, prevention and consequence analysis.